KARAKTERISTIK POLA PENYAKIT PADA NELAYAN PESISIR PULAU AMBON DI KECAMATAN NUSANIWE TAHUN 2022 - Nadya R. J. Riry; Paringotan Y Silalahi; Nathalie E Kalilola; Ritha Tahitu (PAMERI, 2022)
Indonesian people who live on the coast have a distinctive living environment and are different from the city area. Most people in eastern Indonesia such as the Maluku people have to survive amid economic downturns which is one of the main problems causing the health of coastal fishing communities very concerning. Disease patterns faced by coastal fishermen are usually in the form of musculoskeletal disorders, eye disorders, digestive disorders, nutritional problems, Acute Respiratory Infections (ARI), hearing loss, problems with poor habits due to insufficient nutrient consumption, lack of clean and healthy living behaviors, environmental factors that play a role such as a temperature, humidity, extreme weather, being exposed to animal bites in the sea, the duration of contact with seawater, lack of awareness of the importance of the use of personal protective equipment, the habit of smoking and consuming alcohol. This research aims to determine the characteristics of disease patterns in coastal fishermen of Ambon Island in Nusaniwe District in 2022, with a cross-sectional research design and descriptive methods. This research was conducted on coastal fishermen of Ambon Island in Nusaniwe District, sampling was carried out by simple random sampling with a sample of at least 96 respondents. The data was taken using a research instrument in the form of a questionnaire consisting of 21 questions. The results of descriptive statistical analysis showed that the characteristics of the most disease patterns in coastal fishermen of Ambon Island in Nusaniwe District were vulnus/wounds (15.9%), followed by low back pain (12.4%) and myalgia (11.7%). The conclusions of this study show that the characteristics of disease patterns in coastal fishermen of Ambon Island in Nusaniwe District are dominated by vulnus/wounds, low back pain, and myalgia.